REGULARITIES OF CONGELATION ICE DEVELOPMENT IN SUBGLACIAL LAKE VOSTOK - V. Ya. Lipenkov; E. V. Polyakova; A. A. Ekaykin (Лëд и снег, 2015)
Petrographic studies performed on the continuous basis along the two ice cores obtained from holes 5G-1 and 5G-2 at Vostok Station has allowed to characterize with great details the evolution of the ice texture and fabric in the 232-m thick stratum of accreted ice formed from theLakeVostokwater. Conventionally the whole thickness of accreted ice is divided into two strata: lake ice 1 and lake ice 2. Lake ice 1 (3537–3618 m), formed in the sallow strait50 kmupstream of Vostok, is characterized by presence of disseminated mineral inclusions of Lake Vostok sediments, as well as of «water pockets» that represent frozen water inclusions trapped during the ice accretion. The latter constitute less than 1% of the total ice volume, their mean size is about0.5 cm. Gases trapped by «water pockets» during ice formation transform into crystalline inclusions of mixed gas hydrates. Accretion of lake ice 2 (3618–3769 m) proceeds in the deep part of the lake at a very small rate that does not assume trapping of liquid water inclusions and gases.Both strata of accreted ice are formed by orthotropic crystal growth from pure water. The main tendency in the evolution of accreted ice texture is growth of the mean crystal size with depth as the lake ice becomes younger towards the ice-water interface. The high-amplitude variations of crystal size and orientation observed around this general trend are shown to be linked with temporal and spatial variability of the supercooled melt-water flux from the northern part of the lake towards the ice formation site. The presence of supercooled water at the crystallization front supports persistent preferable growth of ice crystals with sub-horizontally oriented c-axes. The lack of supercooled water in turn support persistent growth of ice crystals with vertical or inclined with respect to the crystallization front c-axis orientation. It means that each of these preferred fabric orientations could serve as an indicator of intensity of melt water flux towards the ice formation site. After completing the isotope measurements on the 5G-2 ice core we plan to use the data on ice texture and fabric obtained in this study together with isotope data for thorough analysis of the peculiarities of water circulation in the southern part ofLakeVostok.